Where courage calls : when calls the heart novel [large type] - Oke, Janette, 1935- (Kennebec Large Print superior collection., 2014)
Beth Thatcher has spent her entire life in the safe, comfortable world of her family, her friends, and the social outings her father's wealth provides. Now she is about to leave it all behind to accept a teaching position in the rugged foothills of western Canada, resolved to put her trust in God and bravely face any challenges that come her way. But the conditions in Coal Valley are even worse than Beth had feared. And as she works to make a difference in the rustic frontier mining town, Beth's heart is torn between two young men.